2002
DOI: 10.1002/rcm.656
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography/mass spectrometric assay of endogenous cellular lipid peroxidation products: quantitative analysis of 9‐ and 10‐hydroxystearic acids

Abstract: A sensitive, specific, accurate and reproducible gas chromatography/mass spectrometry method was developed for the assay of 9- and 10-hydroxystearic acids in samples obtained as cell extracts. The preparation of the samples required specific procedures to allow the analysis of both the free and the conjugated hydroxy acids as the corresponding methyl esters. The quantification used propyl-paraben as the internal standard and monitoring of a specific fragment of each isomeric hydroxy acid methyl ester, and allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…Synthesis of 9-HSA and 9-deutero-9-hydroxystearic acid Methyl 9-oxooctadecanoate and methyl 9-hydroxyoctadecanoate were prepared according to the literature (12). 1 H-and 13 C-NMR spectra were recorded on a Gemini 300 spectrometer (Varian, Palo Alto, CA) at 300 and 75.46 MHz, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of 9-HSA and 9-deutero-9-hydroxystearic acid Methyl 9-oxooctadecanoate and methyl 9-hydroxyoctadecanoate were prepared according to the literature (12). 1 H-and 13 C-NMR spectra were recorded on a Gemini 300 spectrometer (Varian, Palo Alto, CA) at 300 and 75.46 MHz, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A downstream product of ROS is the peroxidized lipid 9-hydroxystearic acid (9-HSA), which we found endogenously produced in human embryonic intestine cells and colon adenocarcinoma as a signaling messenger produced by lipid peroxidation. The amounts of 9-HSA in cancer cells inversely correlating with tumor growth, making it a candidate endogenous mediator of redox signaling in proliferative tissues (Bertucci et al, 2002;Calonghi et al, 2007;Cavalli et al, 1991;Gesmundo et al, 1994;Piretti et al, 1987;Piretti and Pagliuca, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…To unravel the role of ROS scavenging and lipid peroxidation in RPCs, we investigated the in vivo function of 9 -HSA, a known downstream product of lipid peroxidation that we previously demonstrated as a regulator of cellular growth in different human tumor cell lines (Bertucci et al , 2002; Calonghi et al , 2007; Cavalli et al , 1991; Gesmundo et al , 1994). In these studies, we revealed by biochemical and structural modeling studies that, in vitro , 9 -HSA inhibits histone deacetylase 1 (HDAC1) activity by directly binding to its catalytic site (Calonghi et al , 2005; Parolin et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We previously characterized the in vitro role of the 9 -hydroxystearic acid ( 9 -HSA), which was found endogenously produced in human embryonic intestine cells and colon adenocarcinoma as signaling messenger produced by lipid peroxidation (Piretti et al , 1987; Piretti & Pagliuca, 1989). 9 -HSA amounts in cancer cells were found inversely correlating with tumor growth (Bertucci et al , 2002; Calonghi et al , 2007; Cavalli et al , 1991; Gesmundo et al , 1994). We found that in zebrafish, 9 -HSA is endogenously produced and its exogenous administration to RPCs severely altered their differentiation, identifying it as a critical molecule acting downstream of redox signaling events.…”
Section: Introductionmentioning
confidence: 99%